Drug therapy-related problem management (2022)
Background: Unresolved drug therapy-related problems (DTRPs) have economic and clinical consequences and are common causes of patients’ morbidity and mortality. This study evaluated the ability of community pharmacists to identify and resolve DTRPs and assessed the perceived barriers to DTRP identification and resolution. Methods: A cross-sectional study which employed the use of three simulated patients (SPs) visit to 36 selected community pharmacies in 11 local government areas in Ibadan, Nigeria. The SPs played the role of a patient with prescription for multiple ailments (23-year-old male), type 2 diabetes and hypertensive patient with medication packs (45-year-old male) and hypertensive patient with gastric ulcer with a prescription (37-year-old female). They reenacted three rehearsed vignettes when they spoke with the pharmacists. A five-member panel of experts predetermined the DTRPs present in the vignettes (n = 11), actions to take to investigate the DTRPs (n = 9) and recommendations to resolve the DTRPs (n = 9). Pharmacists’ perceived barriers to the identification and resolution of DTRPs were assessed with a self-administered questionnaire. The percentage ability to detect and resolve DTRPs was determined and classified as poor ability (≤30%), fair ability (> 30 - ≤50%), moderate ability (> 50 - ≤70%) and high ability (> 70%). Results: One hundred and eight visits were made by the three SPs to the pharmacies. In total, 4.42/11 (40.2%) DTRPs were identified, 3.50/9 (38.9%) actions were taken, and 3.94/9 (43.8%) recommendations were made to resolve the identified DTRPs. The percentage ability of the community pharmacists to detect and resolve DTRPs varied slightly from one vignette to another (vignette 1–49.3%, vignette 2–39.1%, vignette 3–38.8%). But overall, it was fair (40.9%). Pharmacists’ perceived barriers to DTRP detection and resolution included lack of access to patient’s/client’s medical history and lack of software for DTRP detection. Conclusions: The community pharmacists displayed fair ability in detecting and resolving DTRPs. Several barriers preventing the optimal performance of pharmacist in DTRP identification and resolution were identified including inaccessibility of patient’s/client’s medical history. The regulatory authority of pharmacy education and practice in Nigeria need to mount Continuing Education Program to address this deficit among community pharmacists.